PROCESS SIMULATION AND PARAMETER OPTIMIZATION OF MULTI-LAYER MULTI-PASS WELDED ROTOR - WANG YuChao; ZHU MingLiang; FAN ManJie; HUO Xin; XUAN FuZhen (Jixie qiangdu)
Taking the welded rotor of steam turbine as the research object, a two-dimensional axisymmetric finite element model of multi-layer and multi-pass TIG are welding process was established. By using the double ellipsoidal heat source model, the element birth and death method and the Dflux heat source movement subroutine, the welding process was numerically simulated, and the distribution of temperature field and stress field and the optimization method of welding process were analyzed. The results show that a complex heat load curve was formed after repeated heating and cooling during the multi-layer and multi-pass welding process, and the average stress level of the matrix on both sides increases, which improves the uneven stress distribution of the welds. The stress level of the weld zone of the three passes in the same layer decreased slightly compared with the two passes, but the width of the high stress level zone increased, and the welding deformation increased by about 7.9% at the top and bottom of the groove. The research suggests that the number of welding passes in the same layer has an important influence on the stress and deformation of the welds, which should be selected reasonably.